The switch [videorecording (DVD)] - Gordon, Josh; Speck, Will; Aniston, Jennifer; Bateman, Jason; Wilson, Patrick, 1973-; Goldblum, Jeff, 1952-; Lewis, Juliette; Eugenides, Jeffrey (Lions Gate Entertainment, 2011)
Kassie, a smart, fun-loving single woman, despite her neurotic best friend Wally's objections, decides it's time to have a baby, even if it means doing it herself, with a little help from a charming sperm donor. But, unbeknownst to her, Kassie's plans go awry because of a last-minute switch that isn't discovered until seven years later, when Wally gets acquainted with Kassie's cute, though slightly neurotic, son.